2022
DOI: 10.1080/14999013.2021.1995085
|View full text |Cite
|
Sign up to set email alerts
|

Circumstances Leading to and Characteristics of Belgian Forensic Patients Remitted to Prison

Abstract: In Belgium, when forensic patients infringe their conditional release, they are remitted to prison. Given the poor conditions of detention and the current lack of alternatives, revoking conditional releases has a high impact. However, little is known about which patients are remitted to prison and why. In this article, we compared a sample of remitted patients (n ¼ 50) to a matched control group (n ¼ 48). We found that patients with high actuarial risk factors (as assessed by the Violent Risk Appraisal Guide, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…At 224 days (IQR = 426), median length of stay was below the recommended stay of 18 months to 2 years ( 14 ) and length of stay for prison remittals was significantly shorter (median = 173.5 days, IQR = 367) than for community discharges (Median = 404.0 days, IQR = 830) u = 1,423.0, p < 0.001 ( Table 2 ). Most patients stayed in medium secure services <2 years ( n = 116, 82%), although those remitted to prison were 66% less likely to be have been admitted for “24 months plus” (10 vs. 33%, P =.001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At 224 days (IQR = 426), median length of stay was below the recommended stay of 18 months to 2 years ( 14 ) and length of stay for prison remittals was significantly shorter (median = 173.5 days, IQR = 367) than for community discharges (Median = 404.0 days, IQR = 830) u = 1,423.0, p < 0.001 ( Table 2 ). Most patients stayed in medium secure services <2 years ( n = 116, 82%), although those remitted to prison were 66% less likely to be have been admitted for “24 months plus” (10 vs. 33%, P =.001).…”
Section: Resultsmentioning
confidence: 99%
“…The nexus between the criminal justice system and mental health services differs internationally and, at present, there is little work conducted into understanding the remittal care pathway outside of England and Wales. We are aware a recent body of work in Belgium which sought to understand circumstances by which people are returned to prison from secure psychiatric services ( 13 , 14 ). In this investigation it was observed that all returns to prison were on the basis of the individual subverting security.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation